Knowledge of primary survey on lowering consciousness among Pasar Petisah citizens - Suherman, Jessen; Lubis, Andriamuri Primaputra; Paramita, Deryne Anggia; Nasution, Afrida Aryani (Program Studi Magister Kesehatan Masyarakat Universitas Prima Indonesia, 2024)
Lowered consciousness is a life-threatening condition that necessitates prompt assessment and first aid. One crucial method for addressing such emergencies is the primary survey, which aims to identify and treat life-threatening conditions quickly. Pasar Petisah, one of the largest and busiest markets in Medan, is a high-risk location for such emergencies due to its crowded nature. Therefore, the community at Pasar Petisah needs to have a strong understanding of the primary survey procedure. This study is a descriptive cross-sectional analysis that uses primary data collected through questionnaires. The sample size consists of 97 subjects, selected using non-probability sampling techniques. The results indicate that among the 97 participants, only 3 (3.1%) demonstrated a good level of knowledge about the primary survey, 41 (42.3%) had a sufficient level of knowledge, and 53 (54.6%) had a lacking level of knowledge. Regarding readiness to perform the primary survey, 61 individuals (62.9%) reported feeling prepared, 23 individuals (23.7%) were doubtful, and 13 individuals (13.4%) felt unprepared. Overall, while the community at Pasar Petisah generally lacks adequate knowledge about conducting a primary survey in cases of lowered consciousness, a majority still express readiness to perform the primary survey in emergency situations.